Green Marketing and Sustainability: A Comprehensive Bibliometric Analysis - Kharel, Shreekrishna; Lama, Padam Bahadur (Jana Adarsha Research Journal, 2026)
Green marketing and sustainability emphasize eco-friendly business practices, being an environmentally, socially, and economically responsible organization with an endeavor embracing as a mechanism of fostering innovation and trust among consumers. Thus, this study aims to analyze the academic literature on green marketing and the sustainability field, representing the study period from 2004 to 2024. This study employs bibliometric analysis with Biblioshiny (R Package) and VOS viewer software. The Scopus database of 370 is involved in the study, consisting of research articles published only in the English language, representing the subject area of business, management, and accounting. Further, this study analyzed scientific production, citation, relevant authors, source, affiliation, countries, trend topic, frequent map, thematic map, and bibliographic coupling. The findings of the study revealed a growing trend in the annual scientific publication, showing the highest mean total citation per article and per year in 2011. Moreover, sustainability is reflected as one of the most used keywords, followed by green marketing, depicting the United States of America as a highly contributing country. The most relevant journal is depicted as the Journal of Cleaner Production with a rank of first and a high H-index, followed by Business Strategy and the Environment Journal. The most relevant author found is Rosa Maria Dangelico, and the most globally cited document of Paul. The most relevant affiliation remains Universidade Do Vale Do Rio Dos. The trend topic on sustainability and green marketing gained popularity from 2019 onwards and was found as a highly occurring keyword in the research works of scholars. This study demonstrates the rapid growth of research on the green marketing and sustainability theme, establishing a benchmark for future studies.